Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2474/trol.15.374
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Lubricating Properties of CuO and h-Boron Nitride (h-BN)

Abstract: The purpose of this paper is to study the tribiological behavior of (steel/porous iron), (steel/steel) and (steel/bronze) tribopair with micellar copper oxide, hexagonal boron nitride (h-BN), Lithium grease Liten LT43 and base oil, transformer mineral oil, and mineral oil SN650 as lubricants. The results are discussed in the form of performance such as wear surface, friction coefficient, weld point, limiting load wear and load-carrying capacity. It is found that (steel/bronze) friction pair contacts develop in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Compared to the study on the effect of CuO, h-BN or BNNS on tribological property respectively [12,13,[27][28][29], this paper aims at investigating the tribological performance of cooperation effect of f-CuO and PDA-BNNS used as lubrication oil additive. A synthesis route of CuO@BNNS was proposed, in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the study on the effect of CuO, h-BN or BNNS on tribological property respectively [12,13,[27][28][29], this paper aims at investigating the tribological performance of cooperation effect of f-CuO and PDA-BNNS used as lubrication oil additive. A synthesis route of CuO@BNNS was proposed, in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Nano Cu or CuO has been adopted as lubricant additive in many studies. Researches have demonstrated that Cu or CuO on lamellar structure can markedly enhance the wear-resistance of lubricant oil or self-lubricant composites [2,[25][26][27][28][29][30]. Due to the good dispersion ability of Cu@WS 2 in polyalkylene glycol (PAG), the PAG oil showed better friction-reduction and anti-wear properties than WS 2 and Cu nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation